Comparison of Push-Up Exercise Methods on Push-Up Test Ability in Medical Students at Warmadewa University - Tanjung Subrata; Ni Wayan Rusni; I Nyoman Arie Purwana (Warmadewa University, 2022)
TBM members require muscle endurance to implement their tasks, particularly while performing cardiopulmonary resuscitation (CPR), which requires chest, shoulder, and upper arm muscle endurance. Push up is a type of muscle endurance training for the chest, shoulders, and upper arms that do not require any particular equipment or skills. Therefore, the Push Up Test is required for TBM members, and the results suggest that 62% of 2020 TBM members' abilities are below average. The study was conducted on members of the Warmadewa University FKIK Medical Assistance Team to compare the Push Up workout regiments with the same concentric and eccentric phase tempo (P1) and a slower eccentric phase tempo (P2). The two methods are compared to determine which method is more effective in increasing Push Up Test ability. A total of 46 TBM members were involved in this study. The data was analyzed using the paired t-test to compare muscle endurance before and after the exercise was performed. The push up test used during the screening revealed a decrease in muscle endurance fitness, with of students having normal abilities the previous year, but only 16.4 percent in 2021. The exercise intervention 38% had a significant effect on the push up score, which increased by 4.7 points for male after the intervention, while the push up scores for women increased by 5.6 points (95% CI, 3.32 - 8.01). The results revealed that P2 intervention had a greater influence on changes in push-up scores than P1 intervention (mean change was 5.7 for males and 7.3 for females; mean change was 3.8 for males and 4.0 for females; respectfully). This difference, however, was not statistically significant. It can be concluded that push up training improved push up test ability significantly, whereas the comparison of training methods between P1 and P2 was not significantly different. Keywords: muscle endurance, push up method, push up test